Exploring the mechanisms of Palmer amaranth resistance to protoporphyrinogen oxidase-inhibitor herbicides, dynamics of gender, and management strategies - Borgato, Ednaldo Alexandre (Kansas State University, 2023)
Palmer amaranth (Amaranthus palmeri S. Watson) is a C4, summer annual, dioecious broadleaf plant and is the most economically damaging and troublesome weed in major crops grown in the USA. Currently, Palmer amaranth is reported to have evolved resistance to nine herbicide sites of action, raising the importance of integrating multiple weed management strategies. The objectives of this dissertation were to 1) quantify the relative level and characterize target- and non-target-site mechanism(s) conferring resistance to protoporphyrinogen oxidase (PPO)-inhibitors (e.g., lactofen and fomesafen) in a multiple-resistant Palmer amaranth population from Kansas (KCTR), 2) compare female and male life cycles of Palmer amaranth to identify differences that could be incorporated into management decisions, and 3) understand the interactions between pre-emergence (PRE) herbicides in the absence or presence of cover crops dead (terminated two weeks prior to planting) or “green” (terminated at the planting day) as well as impacts on soybean yield. Dose-response assay confirmed resistance to PPO-inhibitors in KCTR Palmer amaranth, which was 12.7- to 34.5-times less sensitive to these herbicides compared to a known susceptible Palmer amaranth. Analysis of the PPO2 gene (the molecular target of PPO-inhibitors) revealed no known mutations nor increased expression of this gene conferring resistance in KCTR. High-pressure liquid chromatography analyses suggested more metabolism of fomesafen at 48, 72 and 96 hours after treatment in KCTR compared to susceptible plants. Additionally, in the presence of malathion, a cytochrome P450-inhibitor, there was increased sensitivity of KCTR to lactofen, suggesting that the KCTR plants metabolized PPO-inhibitors via P450 activity. Interestingly, PRE applications of the PPO-inhibitors fomesafen, flumioxazin, saflufenacil, and sulfentrazone, resulted in complete control of KCTR. A growth chamber assay of comparative emergence of female and male Palmer amaranth in three populations (KS-1, KS-2, and MS-1) indicated that female seedlings reached 90% emergence with 144 growing degree days (GDD) and males with 150 GDD in KS-1, and in MS-1 females reached 90% emergence with 160 GDD, whereas males needed 190 GDD. However, that pattern was not observed in KS-2, and as the GDD window of difference between female and male emergence was short, anticipated female emergence was not a great opportunity to reduce total female number of plants in the population in order to decrease total seed production. Greenhouse studies using an adapted BBCH scale indicated that the lifecycles of female and male Palmer amaranth were not synchronous, but the differences in reproductive phases revealed patterns that can favor fertility and, therefore, seed production. Field studies with PRE herbicides and cover crop [absent, terminated two weeks before planting (“dead” at planting), or terminated on the planting day (“green” at planting)] suggested that the greater the biomass produced by cover crops, resulted in greater weed suppression early in the season. Cover crop alone, dead or green, provided a minimum of 74% of Palmer amaranth control across four site-year experiments. Combination of PREs with cover crops provided greater Palmer amaranth control at 28 days after treatment. Overall, the outcome of this research suggested that 1) P450-mediated metabolism of PPO-inhibitors confers resistance to this herbicide group; 2) differences in female and male reproductive phases can maximize fertilization and, therefore, increase seed production; 3) the use of cover crops provided greater control in early-season, and combinations of PREs and cover crops were more effective method to control Palmer amaranth.
Keywords: Amaranthus palmeri S. Watson; Cover crop; Cytochrome P450; Development; Emergence; Phenology; Pre-emergence